Exploring Outremer.
1 online resource (cccxxxiv, 34 pages).
Keywords: This collection is published in the Crusades Subsidia series in honour of Professor Adrian J. Boas, an archaeologist, historian and scholar who has contributed widely and significantly to the study and teaching of the Middle Ages. Professor Boas research encompasses the archaeology of the Latin East, military orders with particular emphasis on the Teutonic Order, material culture, architecture and medieval art, historiography, and not least, the Crusades and the Latin East. Exploring Outremer Volume II is a collection of 15 original essays by the leading scholars in the field on the history and archaeology of the Latin East. It covers aspects dealing with the history, archaeology, architecture and function of several castles and fortifications in the Latin Kingdom, and presents new studies on the material, including pottery, numismatics and many other finds. In addition, it includes a chapter dealing with landscape archaeology. This book will appeal to researchers and students alike interested in the Kingdom of Jerusalem and Duchies of Edessa and Antioch, as well as the Crusades and Crusading Orders.